Review of MIGA's Experience with Safeguards and Sustainability Policies (1999-2008) - Liebenthal, Andres (World Bank, Washington, DC, 2017)
The objective of this study is to respond to the overarching question posed for the Independent Evaluation Group's (IEG) evaluation of the World Bank Group's (WBG) experience with safeguards and sustainability policies (1999-2008), based on experience of the Multilateral Investment Guarantee Agency (IEG 2010): how effective has the safeguards policy framework of the WBG been in preventing and mitigating adverse environmental and social impacts? The study is organized in four Chapters. Chapter one introduces the objective of the study, outlines the evolution of the Multilateral Investment Guarantee Agency's (MIGA) sustainability framework, summarizes highlights from earlier evaluations and describes the approach for the study. Chapter two reviews MIGA's implementation of the sustainability framework's processes, including the projects initial screening and review, monitoring and supervision. Chapter three reviews the outcomes from MIGA's implementation of its environmental and social policies, to the extent that they can be discerned from the available information. Chapter four presents some concluding reflections.